The Use of Digital Media in Supporting Elementary Students' Learning Motivation in Science and Social Studies - Rifka Amalia; Sarah Fazila; Maya safitri (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
This study was motivated by low learning motivation among fourth-grade students in Science and Social Studies (IPAS) lessons, associated with limited variation in instructional media and predominantly teacher-centred practice. Preliminary observation at SD Negeri 4 Tanah Luas showed that of 25 fourth-grade students, only about 32% were actively attentive during lessons. This study aimed to describe how digital media were implemented, to characterise students' learning motivation, and to examine how digital-media use related to that motivation in IPAS lessons. A descriptive qualitative approach was used, with data collected through classroom observation, semi-structured interviews, and documentation involving the classroom teacher and 8 purposively selected fourth-grade students. Data were analysed using the Miles and Huberman interactive model (data reduction, data display, and conclusion drawing) and validated through source and method triangulation. The findings show that digital media were implemented mainly through instructional videos and interactive PowerPoint presentations displayed via laptop and projector, and that their use was associated with a perceptible shift in student behaviour from passive attention at the outset toward greater visual attentiveness, note-taking, questioning, and enthusiasm as lessons progressed. Students' positive response was most closely linked to the visual and audiovisual elements of the media (images, short videos, and simple animation) rather than to the technology itself. Supporting factors included available hardware and teacher competence, while constraints included technical disruptions, uneven student comprehension, and limited preparation time. These findings suggest that digital media can support, rather than guarantee, increased learning motivation in elementary IPAS instruction, contingent on how the media is pedagogically integrated.